Growth, Yield, and Fiber Morphology of Kenaf (Hibiscus Cannabinus L.) Varieties Influenced by Different Levels of Npk Fertilizers - Rabar Fatah Salih (Green Engineering Society, 2022)
Different levels of NPK fertilizer were used to improve the growth, yield, and fiber morphology of two kenaf varieties. Therefore, a field experiment was conducted in the summer season of 2021 at the Grdarasha Field, College of Agricultural Engineering Sciences, Salahaddin University-Erbil. The results revealed that adding NPK at the rate of 100 kg/ha caused improved growth and yield characteristics includes; plant height, stem diameter, leaf number, and total fresh stem yield by almost (3.35 m, 25.88 mm, 250.10, and 246.93 t/ha), respectively. While, the best values of fresh and dry matter of core and bast fibers were recorded when NPK was applied at the proportion of 150 kg/ha which were (98.40, 57.80, 39.73, and 15.13 t/ha), respectively. Morphological properties of the kenaf bast fiber were also improved by adding NPK fertilizer. Both levels of NPK 100 and 150 kg/ha were noted to be the best for enhancing kenaf bast fiber compared to the control treatment. Finally, based on the results could recommend the farmers to use NPK fertilizer as a factor to increase fiber yield and improve its quality.